Jakość komunikacji w związku a kompensująca rola aktywności w sieci - Siemiątkowska, Kinga; Obrębska, Monika (Człowiek i Społeczeństwo, 2020)
The main purpose of this study was to check whether there are relationships between the partner’s communication behaviours and online activity. The aspect of online activity was divided into: self-disclosure, support-seeking, making and keeping interpersonal contacts. To measure it, an authorial tool was used, called the Questionnaire of Activity in The Internet’s Social Space. In order to measure the partner’s communication behaviours, the Communication in Marriage Questionnaire (Kaźmierczak and Plopa) was used. It includes the following dimensions: support, commitment, depreciation. It was assumed that the partner’s depreciation will correlate positively, and both the partner’s support and commitment negatively with individual dimensions of online activity. The group of respondents consisted 85 women and 63 men, aged 19 to 71. The results showed that there is a positive correlation between partner’s depreciation and also a negative correlation between partner’s support and online supportseeking. No other hypotheses regarding the relationship between partner’s communication and online activity were confirmed. The correlation between the partner’s commitment and online self-disclosure turned out to be positive and therefore opposite to the assumption. Age was considered a variable that could have an impact on this unexpected result, as it negatively correlates with both the partner’s commitment and all dimensions of online activity.